Akronim dalam Komunitas Motor di Kota Merauke - Narahawarin, Margaretha F. (Kajian Linguistik, 2017)
This research will identify, classify, and analyze based on the phenomena of words formation. The data has been collected from some interviews of the motorcycle community members. Theories used in this research by Sampurno and Finoza.The results of this research shows that the acronym used exclusively in the motorcycle community. According to the form of an acronym, there are four forms, namely: form initial characters of the word, syllable form, form initial character of the word and syllable, phrases form. And to the function in this research that acronym as a shorthand phrase or name, slogan or humor, distinguishing origin of a words and meaning.Keywords: acronym, form, function, community